Pharmacokinetics and Pharmacodynamics of the Combination of Rhein and Curcumin in the Treatment of Chronic Kidney Disease in Rats - Xiaoying He; Guowei Li; Yuanyuan Chen; Qiming Xiao; Xinwei Yu; Xixi Yu; Xiaoyang Lu; Zheng Xiang (Frontiers Media S.A., 2020)
Objectives: The interaction between the components of traditional Chinese medicine (TCM) is an important basis for their synergy. Rhein and curcumin exert various pharmacological activities, including anti-tumour, anti-inflammatory, antioxidant, anti-fibrosis and renoprotective effects. However, no investigation has reported the synergistic anti-fibrosis effect yet. This study aims at determine the pharmacokinetics and pharmacodynamics of the combination of rhein and curcumin in the treatment for chronic kidney disease in rats.Design: Fifty two male Sprague-Dawley (SD) rats were randomly divided into rhein group, curcumin group and their combination group for pharmacodynamics studies. HE and Masson staining was conducted to observe the changes of renal morphology. Kits were used to detect the level of urea nitrogen (BUN) and creatinine (Scr). For pharmacokinetic study, 36 SD rats were randomly divided into rhein group, curcumin group and a combination group, the content of rhein and curcumin in plasma and renal tissue was determined by ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). In additon, molecular docking method and cell experiments was used to disclose the interaction mechanism between curcumin and rhein.Results: The pharmacodynamic results showed that the degree of renal fibrosis was improved obviously by co-administration rhein and curcumin. Meanwhile, compared to single administration, the Cmax and AUC of rhein and curcumin in plasma and renal tissue were enhanced significantly after co-administration. Moreover, the result of molecular docking and cell experiments showed that both two compounds could interact with P-gp, CYP2C9 and CYP2C19.Conclusion: Together, these findings demonstrated that rhein and curcumin had a synergistic effect in ameliorateing chonic kidney disease, providing an important explanation on the synergistic mechanism of curcumin and rhein from a pharmacokinetic viewpoint.